Store-operated Ca2+ entry and vascular smooth muscle remodeling - Trebak, Mohamed (Henry Stewart Talks, 2012)
Store-operated Ca2+ entry (SOCE), Measuring SOCE, The whole-cell current mediated by SOCE, ICRAC, The molecular players and mechanisms of activation of SOCE, Vascular Smooth muscle cell (VSMC) remodeling, VSMC organization and function, VSMC contribution to vascular disease, VSMC remodeling in restenosis, VSMC remodeling and expression of ion channel/transporters, SOCE and VSMC remodeling, Role of STIM1 and Orai1 in VSMC SOCE and ICRAC, STIM1 and Orai1 upregulation in VSMC from injured rat carotid vessels, Role of STIM1 and Orai1 in driving VSMC remodeling in vivo, STIM1- and Orai1-mediated SOCE and NFAT activity in VSMC, STIM1 and Orai1 and SOCE in response to the potent proliferative and migratory agonist, PDGF